ALDH2 attenuates myocardial pyroptosis through breaking down Mitochondrion-NLRP3 inflammasome pathway in septic shock - Zhang, Ying; Lv, Ying; Zhang, Qingju; Wang, Xingfang; Han, Qi; Liang, Yan; He, Simeng; Yuan, Qiuhuan; Zheng, Jiaqi; Xu, Changchang; Zhang, Xiangxin; Wang, Zichen; et al. (Frontiers in Pharmacology, 2023)
Cell survival or death is critical for cardiac function. Myocardial pyroptosis, as a newly recognized programmed cell death, remains poorly understood in sepsis. In this study, we evaluated the effect of ALDH2 on myocardial pyroptosis and revealed the underlying mechanisms in sepsis. We established a septic shock mice model by intraperitoneal injection of Lipopolysaccharide (LPS, 15 mg/kg) 12hrs before sacrifice. It was found that ALDH2 significantly inhibited NLRP3 inflammasome activation and Caspase-1/GSDMD-dependent pyroptosis, which remarkably improved survival rate and septic shock-induced cardiac dysfunction, relative to the control group. While ALDH2 knockout or knockdown significantly aggravated these phenomena. Intriguingly, we found that ALDH2 inhibited LPS-induced deacetylation of HADHA by suppressing the translocation of HADC3 from nuclei to mitochondria. Acetylated HADHA is essential for mitochondrial fatty acid β-oxidation, and its interruption can result in accumulation of toxic lipids, induce mROS and cause mtDNA and ox-mtDNA release. Our results confirmed the role of HDAC3 and HADHA in NLRP3 inflammasome activation. Hdac3 knockdown remarkedly suppressed NLRP3 inflammasome and pyroptosis, but Hadha knockdown eliminated the effect. ALDH2 inhibited the translocation of HDAC3, protected ac-HADHA from deacetylation, and significantly reduced the accumulation of toxic aldehyde, and inhibited mROS and ox-mtDNA, thereby avoided NRLP3 inflammasome activation and pyroptosis. This study provided a novel mechanism of myocardial pyroptosis through mitochondrial HDAC3/HADHA-NLRP3 inflammasome pathway and demonstrated a significant role of ALDH2 as a therapeutic target for myocardial pyroptosis in sepsis.